Meta-Synthesis of Teacher’s Self-Concerns: Organizational Management - Naziri, , Fazidah (International Journal of Psychosocial Rehabilitation, 2020)
The world of education system through highly tractional transfiguration was introduced in the Malaysia Education Blueprint 2013-2025. This transformation provides a challenge for all professionals in the field of teaching and thus creates a phenomenon of concern within themselves. This study is a meta-analysis to look at the aspects of self-concern teachers in organizational management at school. A total of 13 articles in 2018 were selected in this study. Some themes in the teacher’s own concerns have been synthesized based on the selected articles studied. Findings show teachers’ professionalism through teacher’s self-esteem gained through technology integration, student management, self-esteem, lifelong learning and social needs within the organization. In addition to these findings, teacher’s self-concern also strengthens the well-being of teachers in the current education system.